2013
DOI: 10.5012/bkcs.2013.34.9.2711
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Investigation of the Effects of Concentration on Hydrogen Bonding in Aqueous Solutions of Methanol, Ethylene Glycol and Glycerol

Abstract: Hydrogen bonding interaction between alcohols and water molecules is an important characteristic in the aqueous solutions of alcohols. In this paper, a series of molecular dynamics simulations have been performed to investigate the aqueous solutions of low molecular weight alcohols (methanol, ethylene glycol and glycerol) at the concentrations covering a broad range from 1 to 90 mol %. The work focuses on studying the effect of the alcohols molecules on the hydrogen bonding of water molecules in binary mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The empty H-bonding sites are mainly occupied by methanol molecules in the form of W-M H-bonds. Thus the number of W-M H-bonds increases with the concentrationincreases, which has been reported in Ref[1]. That is to say, the increasing concentration of methanol leads to simple H-bonding transfer from water-water complex to methanol-water complex[22].…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The empty H-bonding sites are mainly occupied by methanol molecules in the form of W-M H-bonds. Thus the number of W-M H-bonds increases with the concentrationincreases, which has been reported in Ref[1]. That is to say, the increasing concentration of methanol leads to simple H-bonding transfer from water-water complex to methanol-water complex[22].…”
supporting
confidence: 72%
“…The hydroxyl group of each methanol molecule can simultaneously act as H-bond donor and acceptor, and the methyl group has a negative effect on the formation of H-bonds [5]. The structure arrangement of the methanol/water mixtures has close correlation with the local hydration structure and dynamics of the amphiphilic solutes in the polar solvent [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been a large number of computational studies on glycerol and glycerol–water mixtures, including refs and , experimental studies yielding information on liquid structure are more limited. ,, In the past 4 years, we have completed experimental structural studies of pure glycerol and glycerol–water mixtures at 298 K using a combination of neutron diffraction and computational modeling. Our studies have shown that, at intermediate concentrations ( x g = 0.25–0.50), the mixture segregates on the nanometer length scale to form water-rich and glycerol-rich clusters. , This nanosegregation results in regions that exist as hydrogen-bonded clusters that differ in size across the concentration range. In the concentrated glycerol region ( x g = 0.80), a large glycerol cluster exists that spans the full size of the system.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the decrease of water content in the solutions greatly contributed to the decrease of water activity. On the other hand, a glycerol molecule processes three hydroxyls with variable ability to form hydrogen bonds with water molecules, and the lifetime of hydrogen bonds between glycerol and water is longer than those among water molecules themselves, according to molecular dynamics. , The information mentioned above might also contribute to the reduction of fugacity of water, leading to the decrease of water activity. With such a decrease of water content, the unfavorable effect of water on glycation was released.…”
Section: Resultsmentioning
confidence: 99%